Hepatoprotective Activity Of Fruits Of "Prunus Domestica" - MANOJ SONI,; P. K. MOHANTY,; Y.A. JALIWALA, (International Journal of Pharma and Bio Sciences, 2011)
Extract of Methanol:ethanol (70:30) of Prunus domestica was prepared and tested for its hepatoprotective effect against Paracetamol and CCl4 induced hepatitis in rats . Alteration in the levels of biochemical markers of hepatic damage like SGPT, SGOT, ALP,Total bilirubin, direct bilirubin and tissue LPO, GSH, catalase and SOD were tested in both treated and untreated groups. Paracetamol (2 g/kg) and CCl4 (1.5ml/kg) has enhanced the SGPT, SGOT, ALP, Total bilirubin and direct bilirubin and tissue level of GSH. Treatment with extract of P. domestica fruits (150 mg/kg and 300 mg/kg) has brought back the altered levels of biochemical markers to the near normal levels in the dose dependent manner.